2010
DOI: 10.1111/j.1600-0501.2010.01955.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on gene expression and osseointegration in rats

Abstract: Although systemic exposure to nicotine did not affect rat bone development, bone wound healing around the implant after placement was affected. These findings suggest that nicotine might inhibit the bone matrix-related gene expressions required for wound healing and thereby diminish implant osseointegration at late stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 33 publications
3
25
0
3
Order By: Relevance
“…42 This result could be linked to those found in the present study. By corroborating studies of different methodologies, the present study showed that the smoking habit was linked to decreased BSP expression 17,40 and OCN. 37,39 Once BMPs modulate further expression of osteogenic markers, this could affect the mRNA production of BSP, as observed in vivo in human bone in the present study.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…42 This result could be linked to those found in the present study. By corroborating studies of different methodologies, the present study showed that the smoking habit was linked to decreased BSP expression 17,40 and OCN. 37,39 Once BMPs modulate further expression of osteogenic markers, this could affect the mRNA production of BSP, as observed in vivo in human bone in the present study.…”
Section: Discussionsupporting
confidence: 69%
“…Nicotine stimulated the deposition of Ca 2+ in ROB-C26 cells, which are characteristic of the early stage of cell differentiation, and decreased the deposition of Ca 2+ in MC3T3-E1 cells, which are characteristic of the late stage of differentiation of osteoblasts. 38,41 The same time-dependent effect of tobacco on healing was observed in the study by Yamano et al 17 They observed an increased expression of BMP-2, BSP, and type II collagen mRNA in bone harvested from around titanium implants installed in the tibias of rats after 2 weeks. After 4 weeks, in a ''mature'' bone healing area, genes, including BMP-2, BSP, OPN, type II collagen, and core-binding factor subunit a-1, were less expressed.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…There is documented evidence of the detrimental effects of nicotine on wound healing. Delivery of nicotine in a rat model caused significant down-regulation in the expression levels of osteopontin, type l collagen, bone morphogenic protein-2, bone sialoprotein and core-binding factor α-1; compared with controls [14]. It has been reported that nicotine alters epigenetic control and leads to abrogated DNA methylation and histone modifications, which could subsequently perturb transcriptional regulation critically important in cellular transformation.…”
Section: Introductionmentioning
confidence: 96%
“…In a study made by Rodriguez-Argueta et al [20], they discussed how the cigarette components affected the bone vascularization, the nicotine is a potent vasoconstrictor that reduces blood flow and nutrient delivery to healing sites, causing tissue glucose reduction and acidosis. The carbon monoxide also reduces the oxygen-carrying capacity of erythrocytes, and hydrogen cyanide causes tissue hypoxia [20,24,27]. Additionally, the very poor systemic health did not allow an adequate treatment and she did not respond to several attempts.…”
Section: Discussionmentioning
confidence: 99%